Mikroperimetri - Şentürk, Fevzi (My University, 2017)
Teknolojideki son 10 yılda gerçekleşmiş olan hızlı gelişmeler retinal hastalıklara yaklaşımlarımızı pozitif yönde etkilemektedir. Bu teknolojilerden birisi mikroperimetridir. Mikroperimetri perimetrik retinal hassasiyet haritasını fundus resmi üzerine monte ederek patolojilerin daha iyi lokalize edilmesini sağlar. Ayrıca fiksasyon özelliklerini (lokalizasyon ve stabilite) kolay ve kesin olarak mikroperimetri ile belirleyebiliriz. Mikroperimetri maküla hastalıklarının tanısında ve yeni ilaçların tedavisinin değerlendirilmesinde detaylı bilgiler vermektedir. Bu derlemede literatürdeki mikroperimetri çalışmaları özetlenmektedir.

The rapid progress in retinal diagnostic technologies has positively modified our approach to retinal disorders. One of these approaches is microperimetry. Microperimetry has the ability to overlay a perimetric retinal sensitivity map on fundus photograph allowing better localization of the pathology. The characteristic of fixation properties (localization and stability) are easily and exactly quantified with microperimetry. Microperimetry provides a more complete assessment of macular function for diagnostic purposes as well as for evaluation of new treatment methods in patients with macular diseases. In this paper, we review the literature encompassing the results of microperimetry.
Microperimetry
Keywords: Mikroperimetri; Görme Alanı; Maküla Hastalıkları; Maküla Fonksiyonu; Fiksasyon; Microperimetry; Visual Field; Macular Disease; Macular Function; Fixation